Description of Personal Factors of Breastfeeding Mothers in Exclusive Breastfeeding for Stunting Prevention at Tawangrejo Health Center, Madiun City - Wahyu Putri; Nur Hatijah; Annas Buanasita; Dian Shofiya (Journal of Nutrition Explorations, 2025)
Background. Stunting is caused by several factors including low breastfeeding practices. Destination. This study aimed to describe the personal factors of breastfeeding mothers associated with exclusive breastfeeding as a stunting prevention effort in toddlers aged 0–2 years at Tawangrejo Health Center, Madiun City.Method. This study used a descriptive design with a cross-sectional approach on 40 breastfeeding mothers of toddlers aged 0–2 years at the Tawangrejo Health Center, Madiun City. Data were collected through validated questionnaires and analyzed univariately and cross-tabulation. Results. Most respondents were 20–35 years old (85%) and had a high school education/equivalent (55%). The majority of mothers have good knowledge (77.5%) and high motivation (85%) in providing exclusive breastfeeding. Good knowledge tends to be possessed by mothers with higher education, productive age, and previous breastfeeding experience. Meanwhile, high motivation is also seen at all levels of education and is highest in mothers with good breastfeeding experience.Conclusion. The majority of breastfeeding mothers at the Tawangrejo Health Center have high knowledge and motivation in exclusive breastfeeding. Factors of age, education, and breastfeeding experience play a positive role in supporting exclusive breastfeeding practices as an effort to prevent stunting.